Three-dimensional printing and metal framework for designing removable partial dentures - A narrative review - Sara Tarek Ahmed (Saudi Journal of Oral Sciences)
Partial edentulism has become more common in proportion to the growing number of elderly people. In clinical practice, a metal-framed removable partial denture (RPD) is frequently utilized, especially for older patients undergoing oral rehabilitation. For many years, partially edentulous patients have been treated with cast metal RPDs made from various alloys. To evaluate the methods of three-dimensional (3D) printing and metal framework for the fabrication of RPDs. This study employed a narrative review structure to evaluate the published studies addressing the fabrication of RPDs with metal frames and 3D printing. The most pertinent studies were gathered using several electronic resources, including Google Scholar, Web of Science, Cochrane, and PubMed. The success of patients’ oral rehabilitation can be increased using 3D printing to create RPD frameworks more rapidly, with fewer human errors, less waste, more reproducibility, and higher accuracy.